Preparation and Characterisation of Composite Magnetite Fe3O4-Activated Carbon as Adsorben of Phenol - Lestari, Intan; Yohana, Agnes Vionita; Farid, Faizar; Gusti, Diah Riski (Jurnal Riset Kimia, 2022)
Preparation and characterization of magnetite Fe3O4-palm shell activated carbon composite has been carried out as an adsorbent of phenol compounds. Composites were preparation using the co-precipitation  method by mixing Fe3O4 magnetite and suspension of activated carbon in water at 2:1 ratio by co-precipitation method. The functional groups, morphology and magnetization of the composites were characterized by FTIR, XRD, SEM-EDX and VSM. The XRD characterization result showed that the irregular activated carbon diffraction pattern on the composite showed that the carbon structure was amorphous and the peak was typical of Fe3O4 at an angle of 2θ 35.3961˚ with the distance of the diffraction plane or d = 2.53387Ǻ. VSM characterization shows the magnetic properties of magnetite are super paramagnetic with the resulting magnetization value of 15.93 emu/g, the remanence value (Mr) is 1.79 emu/g and the coercivity value (Hc) is 131.64 Oe. Adsorbent used for phenol adsorption with optimum at pH 6 with adsorption capacity was       6.71 mg/g, 120 minute contact time with adsorption capacity was 9.63 mg/g and the amount of phenol absorbed reached equilibrium a concentration of 300 mg/L of phenol with an adsorption capacity is 58.6 mg/g. The kinetics parameter showed that the adsorption followed pseudo second-order model.